The destructive role of excessive society interference in personal life (T. Malyarchuk "We are. A collective archetype") (Literatures of the World: Poetics, Mentality and Spirituality, 2013)
The paper examines the problem of coexistence an independent creative indi-vidual and society. Particular attention is drawn to displaying psychological aspect of the modern city, uniformity of social behavior and attempts to resist human crowdslaws. The motives of outstanding personality’s loneliness and marginality in the real world are leading in the book.
Keywords: personality; community; city; morality; problem